Influence of metabolic syndrome and diabetes on progression of calcific aortic valve stenosis. (1st October 2017) - Testuz, Ariane; Nguyen, Virginia; Mathieu, Tiffany; Kerneis, Caroline; Arangalage, Dimitri; Kubota, Naozumi; Codogno, Isabelle; Tubiana, Sarah; Estellat, Candice; Cimadevilla, Claire; Vahanian, Alec; Messika-Zeitoun, David
Abstract: Background: Determinants of the progression of aortic stenosis (AS) remained unclear. Metabolic syndrome (MetS) and diabetes are suspected to play an active role but literature is scarce and results conflicting. We sought to assess their impact in an ongoing prospective cohort of asymptomatic patients with at least mild AS. Methods: We enrolled 203 patients (73 ± 9 years, 75% men) with at least 2 years of follow-up. Risk-factors assessment was performed at baseline. Annual progression was calculated as [(final-baseline measurements)/follow-up duration] for both mean pressure gradient (MPG) and degree of aortic valve calcification (AVC) measurements. Results: Ninety-nine patients (49%) had MetS and 50 (25%) had diabetes (including 39 with MetS). After a mean follow-up of 3.2 ± 1.2 years, AS progression was not different between patients with and without MetS either using MPG (+ 3 ± 3 vs. + 4 ± 4 mm Hg/year, p = 0.25) or AVC (+ 211 ± 231 vs. + 225 ± 222 AU/year, p = 0.75). Same results were obtained for patients with diabetes (3 ± 3 vs. 4 ± 4 mm Hg/year p = 0.53, 187 ± 140 vs. 229 ± 248 AU/year p = 0.99). MetS had no impact on AS progression in all tested subgroups based on age, statin prescription, valve anatomy and AS severity (all p ≥ 0.10). Conclusion: In our prospective cohort of AS patients, we found no impact of MetS or diabetes on AS progression. Although MetS and diabetes should be actively treated, no impact on AS progression should be expected. Our results support the theory that if cardiovascular risk-factors may play a role at the early phase of AS disease they have no or limited influence on AS progression.